Kajian Perkembangan Teknologi Sistem Kendali Kemudi Kapal Berbasis Internet of Things Berdasarkan Regulasi IMO - Arif Rakhman Suharso; Anang Budhi Nugroho; Rizka Nur Miftakhul Ulum (CV. Indie Press Edutaste, 2026)
This study examines the application of Internet of Things (IoT) technology in ship steering systems to support maritime safety and improve operational efficiency. The research employs a literature review method by analyzing scientific journals, international standards, and previous studies related to ship steering systems and IoT technology in the maritime sector. The results indicate that the integration of digital sensors, GPS, and real-time monitoring systems can improve steering accuracy, maneuvering capability, and operational supervision effectiveness. In addition, IoT technology supports early fault detection and enhances the reliability of ship equipment. The implementation of this technology also has the potential to support compliance with maritime safety standards established by the International Maritime Organization (IMO). Therefore, IoT technology can be considered a promising solution for developing safer and more efficient ship steering systems.